Fabrication of a repulsive-type magnetic bearing using a novel arrangement of permanent magnets for vertical-rotor suspension - Mukhopadhyay, S. C.; Donaldson, J.; Sen Gupta, G.; Yamada, S.; Chakraborty, C.; Kacprzak, D. (Institute of Electrical and Electronics Engineers, 2003)
A repulsive-type magnetic bearing system has been fabricated in which the rotor of a vertical-shaft-type motor is levitated due to the repulsive force between two sets of permanent magnets. A novel arrangement of permanent magnets has been reported here, which has made the suspension of the rotor possible. The system is planned to be applied for pumping milks and other related products in the New Zealand dairy industry.